Cyclized-polyacrylonitrile modified carbon nanofiber interlayers enabling strong trapping of polysulfides in lithium–sulfur batteries. Issue 33 (5th August 2016) - Li, Qing; Liu, Ming; Qin, Xianying; Wu, Junxiong; Han, Wenjie; Liang, Gemeng; Zhou, Dong; He, Yan-Bing; Li, Baohua; Kang, Feiyu
Abstract : A CP@CNF interlayer for lithium-sulfur batteries was fabricated by casting CPAN on the surface of CNFs using a facile dip-coating and subsequent thermal cyclization treatment. Abstract : Lithium–sulfur (Li–S) batteries are seriously constrained by the diffusion and crossover of intermediary product polysulfides and their further reductions on the anode surface. Although carbon-based interlayers have been widely used to inhibit the detrimental shuttle effect in Li–S batteries, the weak physical adsorption of pure carbon materials for trapping polysulfides still leads to low recycle efficiency of active species and short cycle life for cells. Herein, we report a cyclized-polyacrylonitrile-cast carbon nanofiber (CP@CNF) film as an interlayer in Li–S batteries. By exploiting the CP@CNF interlayer, the batteries assembled with bare sulfur cathodes deliver superior rate capability and cycle stability. The reversible capacity could be maintained at 710 mA h g −1 after 200 cycles at 0.3C and a capacity of 560 mA h g −1 can be obtained even at a 2C rate. The improved performances are attributed to both the abundant pyridine groups in the cyclized polyacrylonitrile matrix, which can entrap polysulfides by strong interatomic attraction, and the three-dimensional porous conductive network composed of the carbon nanofiber skeleton and conjugated polymer matrix, giving rise to highly effective transfer pathways for electrons and ions.